Study of Public Open Space Circulation Patterns in Mall Building - Putri Meka Mutya Fhadilla; Satriya Wahyu Firmandhani (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2022)
The lack of open space due to land competition in the area which ultimately causes a lack of gathering activities for the community, so that with the movement of people who originally gathered in open spaces are now starting to move or turn into modern malls. This certainly encourages the development of malls that can be integrated with public open spaces as a gathering place for the community. There are several malls that have been tried to be integrated into malls with the concept of public open space, including The Park Mall Solo, Kelapa Gading Mall in Jakarta and Cihampelas Walk in Bandung. The purpose of this study is to determine the role of circulation patterns that can affect or form open spaces for malls. The method used is a qualitative descriptive method with a case study approach. The analysis was carried out by analyzing and comparing the circulation patterns of the three malls in combining malls with open spaces. The results of this study indicate that the circulation pattern uses covert retail which is arranged in a linear manner, so that visitors can pass through a retail space that has a semi-open circulation form.